Removal of Cu(II) and Cr(VI) from aqueous solutions by water lilies (Nymphaea spontanea) - Choo, Tze Pei (2001)
This study describes an investigation using water lilies (Nymphaea spontanea) to remediate heavy metals (Le. chromium and copper) from aqueous solutions and electroplating waste. Laboratory tests were conducted to evaluate the effect of different ages of water lilies in removing chromium and the efficiency of water lilies in accumulating different metal ions (i.e. chromium and copper) at various concentrations. Phytotoxicity tests on the test plants were also conducted to determine the plant tolerance towards these metal ions. The absorption of metal ions by aquatic plants depends on the nature and the amount of aquatic plants, their stage of development, as well as the metal ion content and the presence of other dissolved substances. This study shows that plant age has significant effect on the removal and accumulation of chromium. Plants of 9 weeks old appeared to accumulate the most chromium followed by 6 and 3 weeks old plant. The roots of water lilies play an important role in the uptake of metal ions and the results show that metal accumulation in water lilies follow the order: roots > leaves> petioles. Water lilies are capable of accumulating substantial amount of chromium. up to 5956 µg/g, and copper, up to 10615 µg/g, and it is shown that copper is removed more rapidly than chromium. The preferential accumulation of copper over chromium is probably due to the selective nature of these plants and the chemical behaviour of the metal ions. Removal of metals by water lilies is more efficient when the metal is present singly in the solution than in mixed metal solution or waste solution. Results also show that copper is more toxic to water lilies when compared to chromium.